Extremities of the N-terminus of envoplakin and C-terminus of its linker subdomain are major epitopes of paraneoplastic pemphigus. Issue 1 (October 2016) - Wang, Xue; Chen, Tiancheng; Zhao, Junyu; Peng, Yang; Chen, Xixue; Tu, Ping; Zhu, Xuejun; Liu, Zhi; Wang, Mingyue
Highlights: Envoplakin1-141 and envoplakin1684-1784 are finer epitopes of paraneoplastic pemphigus. Anti-envoplakin213-377 antibody increases in patients with bronchiolitis obliterans. Anti-envoplakin213-377 antibody increases in patients with lichen planus-like lesions. Abstract: Background: Autoantibodies against N-terminal domains and linker subdomains of envoplakin (EVPL) and periplakin (PPL) were frequently detected in sera of paraneoplastic pemphigus(PNP) patients. Objectives: To further investigate finer epitopes of EVPL and PPL, and evaluate their associations with clinical aspects of PNP. Methods: We produced 12 overlapping truncated fragments of these regions in Escherichia coli, and measured their reactivities to sera of 65 PNP patients and 50 healthy volunteers by enzyme-linked immunosorbent assays (ELISA). Then appropriate statistics were performed to evaluate the correlation between antibodies against different fragments and clinical information of patients. Results: EVPL-N1 (aa1-141) and EVPL-L3 (aa1684-1784) were recognized by PNP sera at the same sensitivity of 75.38% (49/65) with specificities of 98% and 92%, respectively. Although neoplasm types were not associated with any fragment, the ELISA of these fragments and indirect immunofluorescence on rat bladder complemented each other in detecting PNP. Meanwhile, levels of autoantibodies against EVPL-N3 were elevated with PNP accompanied with bronchiolitis obliterans or presented with lichen planus-like lesions ( P < 0.05). No influence of autoantibodies against any fragments on prognosis of the patients was observed by Cox regression test, though antibodies against some fragments were higher in the dead patients. Conclusions: The study proved antigenic epitopes were mainly concentrated on EVPL-N1 and EVPL-L3 in PNP. Autoantibodies against EVPL-N3 might associate with those patients accompanied with bronchiolitis obliterans or presented with lichen planus-like lesions.